Overexpressed Wnt-7a acts as a potential antitumor immune modulator and predicts poor prognosis in HNSCC - Hui-chao Jiang; Ya Gao; Shu-yan Wang; Yong-lan Zhao; Hai-peng Sun (Heliyon)
Immune checkpoint inhibitor (ICI) has become the first-line treatment of advanced head and neck squamous cell carcinoma (HNSCC), which has a relatively poor clinical prognosis and high mortality. However, only a proportion of patients respond well to ICI therapy. Identifying reliable predictive markers and potential targets to enhance the efficacy of ICI is of great importance. In this study, we systematically screened potential genes related to poor prognosis in HNSCC and Wnt-7a was selected based on results from multiple databases. Wnt-7a was overexpressed in HNSCC tissues and was associated with shorter overall survival. Human tissue samples and further bioinformatic analysis showed that Wnt-7a may be expressed in T cells and inhibited the infiltration and function of cytotoxic T cell response, both directly and indirectly through decrease the infiltration of Th1, Th17 cells and increasing the infiltration of Tregs. Genes that can directly interact with Wnt-7a were also identified. Surprisingly, 8 out of 9 genes identified were found to participate in the modulation of anti-tumor immunity. In addition, our study suggested that Wnt-7a, as a canonical Wnt ligand, could exert its function via regulating Wnt signaling and related mechanisms. Taken together, these results strongly support that Wnt-7a is a strong predictor of prognosis and ICI efficacy, and could be a promising potential target for enhancing the therapy response.